Localized institutional actors and smallholder irrigation scheme performance in Limpopo Province of South Africa - Mwadzingeni, Liboster; Mugandani, Raymond; Mafongoya, Paramu (MDPI AG, 2021)
Poor performance bedeviling SISs in South Africa is attributed to poor institutional integration, consequently impacting service delivery. Despite this, local institutional actors (LIAs)’ role has not been documented as a potential entry point to address poor performance and hence increase SISs’ sustainability. This study sought to assess the role of LIAs on the performance of the Tshiombo irrigation scheme (TIS). Structured questionnaires, key informant interviews (KIIs), and focus group discussions (FDGs) were used for data collection. Yield data for sweet potato, the main crop grown in the scheme, was measured as a proxy indicator for performance. Ordinary least square regression model was used to assess the relationship between LIAs and scheme performance after reducing the data using principal component analysis. The study revealed that institutional factors such as community credit support, academic extension support, academic institution market and input support, community maintenance support, and community input support positively and significantly (at 5% level) improved the yield by a margin of 0.49, 0.12, 0.1, 0.36, and 0.10. Assessing institutional actors’ interaction within each scheme will help develop linkages that will enable sustainability of irrigation schemes. Out scaling of research on LIAs on irrigation scheme performance enhances scheme performance.